2019
DOI: 10.3390/met9060702
|View full text |Cite
|
Sign up to set email alerts
|

Transient Evolution of Inclusions during Al and Ti Additions in Fe-20 Mass pct Cr Alloy

Abstract: The transient evolution of inclusions during Al and Ti additions in a Fe-20 mass pct Cr alloy was investigated using polished cross sections and electrolytic extraction. After Al addition, the evolution of Al2O3-based inclusions based upon the area and particle size passed through the following three main stages with time: Particle agglomeration, inclusion floating, and a slow decrease of the remaining Al2O3-based inclusions. Titanium wire was fed into the steel at the end of the floating stage after Al additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Figure 8 shows morphologies of Al 2 O 3 •TiO x inclusions during RH treatment and tundish processes, indicating that there are mainly three types of Al 2 O 3 •TiO x inclusions. The first type is similar to the shape of Al 2 O 3 inclusions, including spherical and polygonal shapes, and the size is usually smaller than 5 µm, as shown in Figure 8a-d Similar morphologies of the first two types of Al 2 O 3 •TiO x inclusions were observed by Dorrer [19], Yang [23], Wang [24], Bai [25] and Yang [26]. The third type of Al 2 O 3 •TiO x inclusions, in which the Al-Ti-O is distributed in the outer part and the Al 2 O 3 is distributed in the inner part, was also reported by Basu [14], Park [20], Wang [27], Doo [28], Qin [29] and Sun [30].…”
Section: Morphological Evolution Of Inclusionssupporting
confidence: 72%
See 1 more Smart Citation
“…Figure 8 shows morphologies of Al 2 O 3 •TiO x inclusions during RH treatment and tundish processes, indicating that there are mainly three types of Al 2 O 3 •TiO x inclusions. The first type is similar to the shape of Al 2 O 3 inclusions, including spherical and polygonal shapes, and the size is usually smaller than 5 µm, as shown in Figure 8a-d Similar morphologies of the first two types of Al 2 O 3 •TiO x inclusions were observed by Dorrer [19], Yang [23], Wang [24], Bai [25] and Yang [26]. The third type of Al 2 O 3 •TiO x inclusions, in which the Al-Ti-O is distributed in the outer part and the Al 2 O 3 is distributed in the inner part, was also reported by Basu [14], Park [20], Wang [27], Doo [28], Qin [29] and Sun [30].…”
Section: Morphological Evolution Of Inclusionssupporting
confidence: 72%
“…In addition, the formation of TiOx inclusions is possible at the steel/slag interface based on Reaction (R3). Many scholars [23][24][25][26][27][28][29][30] have studied the formation mechanism of Al2O3•TiOx inclusions, and their studies are good for analyzing the formation mechanisms of various Al2O3•TiOx inclusions. The schematic of the process is depicted in Figure 14.…”
Section: Formation Evolution Of Inclusionsmentioning
confidence: 99%
“…It can be inferred that the high Cr content in FeCrAl alloys greatly suppresses the formation of Al 2 O 3 inclusions. Bai et al [ 29 ] considered that an increase in Cr content reduces the deoxidization ability of Al in stainless steel. Similarly, Ohta et al [ 30 ] investigated the Al‐O equilibrium in Fe‐10, 20, and 40 mass% Cr alloys and found that the O content increased with increasing Cr content at a given Al content.…”
Section: Discussionmentioning
confidence: 99%
“….41 [29] 0.03 [29] Al 0.025 0.045 0.03 0.033 [3] -6.6 r Al O =0.012, [25] r Al;O O =327 300/T þ 127 [26] r Al Al =-0.001, [3] r O Al =-107 þ 275 000/T, [28] r O;Al Al =47.4 [28] Figure…”
Section: Evolution Process Of Al 2 O 3 Inclusions With Reaction Timementioning
confidence: 97%
See 1 more Smart Citation